Management of psoriasis -ayurveda and allopathy-A review - Nikitha Abraham; Neethu Krishnan; Anjana Raj (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2019)
Psoriasis is a chronic infl ammatory skin disease that affects 2% to 4% of the population. Infl ammatory arthritis develops in approximately 30% of patients with psoriasis and can have a major effect on activities of daily living and quality of life. Peripheral joint involvement in patients with psoriatic arthritis can be oligo articular or poly articular and can cause joint destruction.